Factors influencing career success among women managers: a research framework - Krishnan, Venisa Ratha; Alias, Siti Noormi; Idris, Khairuddin (Human Resource Management Academic Research Society, 2020)
The purpose of this paper is to reviews recent literature on women at work, through an analysis of existing literature, in order to identify factors that contribute to the success of women managers in their careers. This study is based on an extensive review of past research on career success. To conduct the literature review, keywords such as career success, job flexibility, family culture, networking and career success among women managers. Besides that, the ideas of this study arranged according to the year which are from 1988-2019. The paper offers a number of propositions which explains the proposed model of career success among women managers. Future research is recommended to test and validate the framework to provide empirical evidence. The paper yields a new approach in theorizing career success among women managers by integrating the social capital theory and social cognitive career theory. Upon model validation, the paper can offer practical interventions for human resource development (HRD) managers to help women managers in managing the career success.